Isoflavonoid composition and biological activity of extracts from soybean seedlings treated by different elicitors (2018)
ABSTRACT: Time-course and dose-response experiments were carried out to establish the ability for synthesizing isoflavonoids of soybean seedlings (cv. Soyica P34) treated with salicylic (SA) and isonicotinic acids (INA). Then, 25 structurally-related compounds were evaluated for their isoflavonoid-eliciting activity. Next, the antimicrobial and antioxidant activities of EtOAc-soluble fraction from soybean seedlings treated with some synthetic elicitors were determined. Results showed that the concentration of isoflavonoids in soybean seedlings was significantly increased by the application of SA and INA. The major isoflavonoids detected were the malonyl-glycosidic isoflavones, followed by genistin and daidzin. The isoflavone aglycones (genistein, daidzein, and formononetin), coumestrol and glyceollins were found in lower concentrations. Maximum accumulation of glyceollins was detected after 48 and 144 h in soybean seedlings treated with 1.6 mM INA and SA, respectively. EtOAc-extracts from soybean seedlings treated with two structurallyrelated compounds to INA displayed a significant antimicrobial and antioxidant activity. Therefore, INA, SA and structurally-related compounds can be used to increase the amounts of natural antioxidant or antimicrobial compounds in soybean, either to protect the plant directly against pathogens or as a natural source for subsequent isolation of isoflavonoids or bioactive extracts, which have potential application in functional foods or pharmaceutical and personal care products.